Pricing Decision under Dual-Channel Structure considering Fairness and Free-Riding Behavior - Yongmei Liu; Chunjie Ding; Chen Fan; Xiaohong Chen (Discrete Dynamics in Nature and Society)
Under dual-channel structure, the free-riding behavior based on different service levels between online channel and offline channel cannot be avoided, which would lead to channel unfairness. This study implies that the dual-channel supply chain is built up by online channel controlled by manufacturer and traditional channel controlled by retailer, respectively. Under this channel structure, we rebuild the linear demand function considering free-riding behavior and modify the pricing model based on channel fairness. Then the influences of fair factor and free-riding behavior on manufacturer and retailer pricing and performance are discussed. Finally, we propose some numerical analysis to provide some valuable recommendations for manufacturer and retailer improving channel management performance.